Hubungan Proses Persalinan Terhadap Perkembangan Motorik Pada Bayi Usia 4 Bulan Dan 10 Bulan - Pratiwi, Asih; , Umi Budi Rahayu, SSt. Ft. SPd. M. Kes; , Sugiono S.Fis.MH.Kes (2016)
Background: Motor development is the development of a control body movement through the coordination of the activity of the central nervous, peripheral nerves and :muscles. Control the 111(\\, ::I11<e:mnterged from the development of reflex-reflex which started in the womb. •1he development 01" 111010c1o' nsist of 2 1110torthat is differentiated into gross and line motor. The gross 111010ris an aspect of motor development of locomotion (movement) and postures (body position). while the fine motor development is an aspect thai is affected by maturation of neuromuscular coordination. 1110torfunction is good. accurate visual function. and the ability of the intellect nonverbal. Motor development i$ influenced by many factors. both from" ithin and from the outside one is labor. Birthing is consist of2 thai is spontaneous labor and seciio caesarea. Spontaneous birthing cause a baby actively experiencing the reflex was born. while babies who are born in sectio caesarea do not experience a reflex born. Early development in the baby's brain is maturasi influenced by primitive reflex mechanisms which were reflected in the womb. birth reflexes. reflexes after born and natural reflexes. Primitive reflexes of the average will be clouded by a functional movement at the age of 6 months. Primitive:' reflexes of their residence shows the presence or impaired development. Objective: This research was conducted to find out the labor relationship with 1110tordevelopment of infants aged .j months and I() months. Research method: This study uses observational approach case control of retrospective. Measuring instrument used is the II DDST. Su~jCCtS research 30 infants aged 41months and ~O infants aged I() months. Result: Test analysis using Chi-Square with the result p value on 4 month age group is 0.0 II and P value On 10 month age group is 0.127. Conclusion: On 4 1110nthage group the P value < 0.05 which means there is a relationship between birth'ing with the development of motor skills and 10 month age group the P value > (LOS which means there is no relationship between binhing with the development of motor skills. Key words: fine 1110torgross motor. birthing process